Pengembangan E-Modul berbasis Flipbooks pada Materi Globalisasi Kelas XII SMA IT Raudhatul Jannah Cilegon - Azizah, Faizati Nur; Kuntari, Septi; Hardiansyah, Muhammad Agus (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research aims to determine the feasibility and practicality of flipbook-based e-modules in class the. (Sugiyono, 2012:297). This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. In this model, it only reaches the evaluation stage which is obtained from suggestions or comments from validators and students to be used as a reference for improving the product that will be used. The results of the data analysis described above consist of 3 discussions, namely (1) media expert trial results, (2) material expert trial results, and (3) student trial results. The results obtained from the media expert validation data analysis namely the total obtained is 54 out of a maximum total of 75. Based on these calculations, the average product validation obtained by media experts is 72%, so it can be seen that this E-Module product is found between 61-80% (Good) Ahmi validation data analysis material, namely the total obtained is 40 out of a maximum total of 50. Based on these calculations, the average product validation obtained by material experts is 80%, so it can be seen that this E-Module product is between 61-80% (Good). The results of the total student assessment obtained were 2319 out of a maximum total of 2520. Based on the t calculation, an average score of 92% was obtained. It can be seen that this E-Module product is between 81-100% (Very Good).